Word-building concept of German suffixal nouns with metonymical component - Ільчук, О. А. (Studia Philologica, 2019)
If many scientific researches are devoted to the study of lexical and grammatical concepts, then the question of the word-building concept has not been adequately researched in linguistic studies. The purpose of the article is to provide a definition and outline the specifics of the word-building concept, to present the possible typology of word-building concepts on the example of a group of suffixal nouns of modern German with metonymic component. The material of the study is about 3.600 lexical-semantic variants of suffixal nouns of modern German, with the aim of studying word-building concepts, the method of conceptual analysis is used. Under the word-building concept we understand the information structure that contains the conceptual information of the word-building level about the sets of conceptual elements, conceptual structures and schemes used by the subject when creating or using derivative words. The subject has conceptual information of the word-building level about word-building suffixes with a certain meaning, possible derivative units, models of their combination (word-building and cognitive models) and can use during the conceptualization information structures of different types. The bearers of wordbuilding concepts are derived units, and the word-building concept is a morphological concept that consists of concepts of derivative morpheme and of suffix and is subjected to a lexical concept. Word-building concepts of derived nouns are, for example, OBJECT OR OBJECT AS RESULT OF ACTION, PERSON FOR RESIDENCE OR STAY, RESULT OF ACTION, PLACE FOR EXECUTABLE ACTION, where the first part of the name of the word-building concept corresponds to morphological concept of suffixal morpheme (SUBJECT, PERSON, RESULT, PLACE), and the second part is the morphological concept of a derivative morpheme (AS THE RESULT OF ACTION, FOR RESIDENCE OR STAY, OF ACTION, FOR EXECUTABLE ACTION). In general, derived nouns with suffixal formant represent word-building concepts that belong to the group of concepts BEING AND HUMAN ACTIVITY (46 % ), OBJECT (27 % ), PERSON (22 % ), PLACE (4 % ), PLANTS AND ANIMALS (1 % ). Further study of the word-building concept should be continued, in our opinion, by involving other groups of word-building units, including complex ones, which will clarify the proposed definition of word-building concept and establish clear criteria for the separation of word-building concepts.